Neotropical orchid-weevils of the genus Stethobaroides Champion (Coleoptera, Curculionidae, Baridinae) - Prena, Jens (Zootaxa, 2025)
Stethobaroides Champion, 1908 comprises the species of the Stethobaris LeConte complex with an exposed pygidium. The following eight species are recognized in this study, five of them as new to science: Stethobaroides badicrus Prena new species (Costa Rica), S. elcoranus Prena new species (México), S. lauro Prena new species (Costa Rica), S. nudiventris Champion, 1908 (Belize, México), S. permixtus Prena new species (Costa Rica, Panamá), S. piliventris Champion, 1908 (México), S. scutellatus Casey, 1922 (Brazil, French Guiana) and S. villus Prena new species (México). Diorymerellus vigintiestriatus Fonseca, 1957 is a new junior synonym of S. scutellatus. A lectotype is designated for S. nudiventris. Specimens of five Stethobaroides species occurred on 17 genera of epidendroid orchids, most frequently on species of Catasetum and Gongora. One species, provisionally identified as S. permixtus, occurred numerously on Vanilla planifolia Andrews, a commercially important orchid in the Vanilloideae subfamily. Plant associations remain unknown for three species from the Pacific regions of México. Remarks are made regarding Toxpam, a historical collecting site in Veracruz, México.